2012
DOI: 10.1093/jac/dks021
|View full text |Cite
|
Sign up to set email alerts
|

Comparing neonatal and paediatric antibiotic prescribing between hospitals: a new algorithm to help international benchmarking

Abstract: This novel method has the potential to be a useful tool to provide antibiotic use comparator data and requires validation in a large prospective point prevalence study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 14 publications
3
66
1
2
Order By: Relevance
“…In UK survey, 24 different combinations of dose were revealed and the dosing interval varied markedly from 12 to 48 h. In a French survey, we found 25 different combinations of doses and the dosing interval varied from 8 to 48 h. For vancomycin, clinical practice is even more variable in France, as both of continuous infusion and intermittent infusion were routinely used. Our results are also consistent with the previous findings by Porta et al 39 who reported wide variation between four children's hospitals in the type and dose of antibiotic used in paediatrics based on daily prescription data.…”
Section: Discussionsupporting
confidence: 93%
“…In UK survey, 24 different combinations of dose were revealed and the dosing interval varied markedly from 12 to 48 h. In a French survey, we found 25 different combinations of doses and the dosing interval varied from 8 to 48 h. For vancomycin, clinical practice is even more variable in France, as both of continuous infusion and intermittent infusion were routinely used. Our results are also consistent with the previous findings by Porta et al 39 who reported wide variation between four children's hospitals in the type and dose of antibiotic used in paediatrics based on daily prescription data.…”
Section: Discussionsupporting
confidence: 93%
“…Currently, the WHO does not, however, recommend the use of DDDs as measurement in children, but in practice this approach is commonly used since more accurate methods are not available 30. Thus, there are no generally accepted DDDs for children, although some studies have suggested possible DDDs for different ages of children 31 32…”
Section: Discussionmentioning
confidence: 99%
“…One possible way of producing such data would be based on the weight of individual patients. The study by Porta et al 31 (European ARPEC project) suggested age-appropriate DDDs for antibiotics especially for neonates. On the other hand, some studies suggest that adult DDDs in paediatrics may be equal with PDDs or higher 13 14…”
Section: Discussionmentioning
confidence: 99%
“…Die Angabe von DDD/RDD (Defined Daily Doses/Recommended Daily Doses) sind für den Bereich der pädiatrischen Medizin nicht möglich -verschiedene alternative Vergleichsmöglichkeiten des Antibiotikaverbrauchs zwischen pädiatrischen Kliniken werden zurzeit untersucht. [ 17 ] . Diese alternativen Konzepte basieren auf der Erfassung des Antiinfektivaverbrauchs in verschiedenen pädiatrischen Gewichtsklassen [ 17 ] oder "Days of Therapy (DOT)", also Antiinfektivatherapietage für eine spezifi sche Substanz pro 100 stationäre Behandlungstage [ 26 ] .…”
Section: ▼ Klinische Einrichtung Und Eckdatenunclassified
“…[ 17 ] . Diese alternativen Konzepte basieren auf der Erfassung des Antiinfektivaverbrauchs in verschiedenen pädiatrischen Gewichtsklassen [ 17 ] oder "Days of Therapy (DOT)", also Antiinfektivatherapietage für eine spezifi sche Substanz pro 100 stationäre Behandlungstage [ 26 ] . …”
Section: ▼ Klinische Einrichtung Und Eckdatenunclassified